Government as entrepreneur - Link, Albert N.; Link, Jamie R. (New York ; Oxford : Oxford University Press, 2009)
Interest in entrepreneurship and its impact on the economy has recently exploded and while there have been books published on various aspects of entrepreneurship, literature on the role of government has been noticeably absent. This book is the first broad effort to emphasize the entrepreneurial aspects of governments.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Technological innovations -- Government policy -- United States; Entrepreneurship -- Government policy -- United States